Hakea, the world's most sclerophyllous genus, arose in southwestern Australian heathland and diversified throughout Australia over the past 12million years - Lamont, Byron; He, Tianhua; Lim, Sim Lin (CSIRO Publishing, 2016)
Hakea (Proteaceae) currently comprises over 150 species, with two-thirds confined to south-Western Australia (SWA) and the remainder spread throughout Australia, especially along the eastern coast. We constructed a time-based molecular phylogeny for the genus and used area-assignment techniques to trace its biogeographic history. According to our area-cladogram analysis, there is a 95% probability that Hakea arose 18million years ago (Ma) in the sandplains of SWA. From 12 Ma, the genus speciated and migrated into forest and onto granite outcrops within SWA, into the drier centre and then continued to the maritime forests of eastern Australia (EA) 3000km away, and north-east to savanna grasslands. The Nullarbor Plain was an obstacle but it did not prevent eastward migration. Twelve westeast, apparently allopatric, speciation events are identified that coincided with glacial maxima, but more likely represent sympatric speciation in SWA or central Australia, followed by further migration and speciationextinctionspeciation events across central to EA. During the period from 8 to 1 Ma, net speciation has been linear and strong in the sclerophyll shrublands of SWA and, to a lesser extent, the sclerophyll forests of EA. Four lines of evidence (historical distribution of sclerophyllous Proteaceae, historical subjection to aridity, species diversification patterns, relative allocation of drought-adapted traits) support our area-cladogram results that Hakea originated in SWA and gradually spread to all parts of Australia as suitable nutrient-impoverished, and open drought-and fire-prone habitats became available.